Repellent potential of leaf extracts of elettaria Cardamomum maton. (zingiberaceae) against Malarial vector, anopheles stephensi Liston (diptera: culicidae) - BHARAT SHARMA,; NEERU VASUDEVA, (International Journal of Pharma and Bio Sciences, 2018)
Mosquitoes act as the vectors for the serious diseases of mankind. Mosquito bites can cause allergic reaction to the skin. The major approach for the control of vector borne diseases is personal protection from the bites of vector mosquitoes. Repellents are substances that act locally or at a distance from the body, deterring an insect from flying to, landing on or biting human or animal skin. Plants contain bioactive compounds which they use for the prevention of attack of plant eating insects. An economical and practical means of prevention of diseases transmission through the bite of mosquito is application of repellents on the skin. Cardamom is the dried fruit of the tall perennial herbaceous plant, Elettaria cardamomum Maton, and belonging to the family Zingiberaceae. The finely ground plant material was extracted with four different solvents namely ethyl acetate, methanol, hexane and chloroform. The arms of volunteer, only 25 cm2 dorsal side of the skin on each arms were exposed and the remaining area covered with rubber gloves. The crude extracts were applied at 1.0, 2.5 and 5.0 mg/cm2 separately in the exposed area of the forearm and tested against the mosquito Anopheles stephensi. Ethanol was served as the control. Our findings suggested that the leaf extracts of Elettaria cardamomum may be explored as a potential environmental-benign repellent.